(untitled) (Global Journal of Science Frontier Research, 2014)
Rice husks and algae plant substrates were success-fully used to produce biogas. A metal fixed-dome biodigester (bioreactor) was used for the characterization of the biogas generated from these plants wastes. A total of 35 kg of slurry (sludge) made from 5 kg of rice husks and 30 kg of algae were mixed in water in the ratio of 1:6 and fed into the biodigester (bioreactor). The digestion of slurry was undertaken in batch-type anaerobic digestion and mesophilic temperatures range at 29.00 o C -33.45 o C. For over period of 75 days, the cumulative biogas produced from the wastes was 156.25 litres. The percentage of the methane component of produced biogas was 52.3% .The biogas from the seeded rice husk was combustible on the 45 th day.